Retorika Pemerintah dan Respon Masyarakat Studi Kasus di Indonesia dan Filipina - John Haba (Jurnal Masyarakat dan Budaya, 1997)
Greg Acciaioli-Jenifer Nourse (eds). Official Rhetoric-Popular Response Dialogue and Resistance in Indonesia and Philippines, Adalaide: Social Analysis-Journal of Cultural and Social Pracites No.35, April 1994. 164 Halaman